Implementing ALTAEXPERIENCE.ID: A Digital Data Management Approach to Support Strategic Marketing Communication in Music Events - Muhammad Akbaryadi (Golden Ratio of Mapping Idea and Literature Format, 2026)
The study examines the planning of a digital data management system named "ALTAEXPERIENCE.ID" to enhance marketing communication and audience engagement within the music event industry. In the complex digital era, marketing effectiveness relies heavily on targeted interactions and efficient data management. This study employs a project planning methodology supported by empirical survey data from 55 concert-goers and a comprehensive situational analysis, including SWOT and competitor evaluation. The proposed system integrates QR Code technology, the WhatsApp Business API, and digital gamification to create a centralized ecosystem for seamless registration, real-time interaction, and automated data collection. The results reveal that 56.4% of attendees frequently encounter technical issues such as long queues and ticket fraud, while 100% of respondents expressed a high willingness to adopt a digital identity system for improved access and interactive features. Major findings suggest that "ALTAEXPERIENCE.ID" successfully transforms traditional one-way marketing into a participatory "phygital" experience that boosts brand recall and loyalty. The system enables organizers to analyze audience interaction data in real-time, providing actionable insights to refine marketing messages for future events. By bridging the gap between physical and digital engagement, this planning serves as a practical, scalable solution for event organizers navigating the digital transformation.